Tasmim al-Wasail al-Ta’limiyyah li Maharati al-Istima’ khilala Android - Kholis, Muhammad Nur; Ghofur, Abdul; Zaenuri, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2020)
Listening is a skill that has not received much attention in Arabic learning and teaching. This can be seen that only a small number of media is made for teaching listening. Whereas media such as sound recordings are very important for students to get used to listen to Arabic utterances.The purpose of this study is to determine the ideal android application design for Arabic learning focused on listening in the IAIN Surakarta language development center. And then the research method is research and development follow Sadiman model:1. Needs analysis, 2. Setting goals, 3. Developing material, 4. Developing evaluation tools, 5. Products, 6. Validating material and design experts, 7. Final results. The result of this study are the discovery of an ideal design based on Android learning applications with design expert validation of 93.75 and the results of material expert validation of 87.5%. The results of the validation explained that the application of learning skills in Arabic listening was appropriate to be used as a learning media. The application consists of the main components, namely the strategy page, material page and training page. The strategy page contains strategies to answer listening questions about TOSA (Test Of Standart Arabic). The material page contains four audio material related to the type of questions in the TOSA. while the practice page contains the question exercises in accordance with the types already discussed on the material page.